The Influence of BI Rate, Inflation, Exchange, JUB, and Dow Jones Index on IHSG on BEI - Aulya, Deva Tara; Hasmarini, Maulidyah Indira (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The purpose of this quantitative study is to ascertain how the DJIA, inflation, exchange rate, BI Rate, and currency volume affect the Indonesia Stock Exchange's composite stock price index. The research's data set spans the years 2019 through 2023. Methodologically, F and t-tests are used for hypothesis testing in conjunction with multiple linear regression. Furthermore, the research employs the R2 square, with a significant threshold of 5%. In this study, autocorrelation, multicollinearity, residual normality, and heteroscedasticity tests were employed. The money supply and BI rate have no discernible impact on the IHSG. The Dow Jones index, exchange rates, and inflation all have a big impact on the Jakarta Composite Index.